O EXERCÍCIO REGULAR PODE REDUZIR COMPLICAÇÕES DA DOENÇA FALCIFORME (Fiep Bulletin - online, 2016)
This article is part of the activities developed in the Human Physiology discipline and has as objective to reduce the oxidantivo stress through physical exercises that can possibly be used to treat people with sickle cell disease.
Keywords: Physical Exercise Regular; Complications; Sickle Cell Disease.